2016
DOI: 10.1007/s40261-016-0424-9
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine in Patients with ST-Elevation Myocardial Infarction Complicated by Cardiogenic Shock: A Preliminary Randomized Prospective Study

Abstract: Ivabradine in CS complicating AMI is safe, is associated with a short-term favourable outcome and can be effectively administered by nasogastric intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 17 publications
0
36
1
1
Order By: Relevance
“…Higher HR has been shown to predict a worse prognosis in both AHF and chronic decompensated HF [18,19]. After demonstration of reduction of HR with ivabradine in chronic HF [7,8], several studies have suggested a possible role of rapid lowering HR during hospitalization in AHF patients or CS [9][10][11][12][20][21][22][23]. However, few data are available on the hemodynamics of rapidly reducing HR in AHF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher HR has been shown to predict a worse prognosis in both AHF and chronic decompensated HF [18,19]. After demonstration of reduction of HR with ivabradine in chronic HF [7,8], several studies have suggested a possible role of rapid lowering HR during hospitalization in AHF patients or CS [9][10][11][12][20][21][22][23]. However, few data are available on the hemodynamics of rapidly reducing HR in AHF.…”
Section: Discussionmentioning
confidence: 99%
“…However, important hemodynamic parameters, such as PCWP, SAP or CO were not recorded in these studies. In a study by Barillá et al [23], a total of 58 patients with CS as a complication of acute elevation myocardial infarction and HR > 75 bpm were randomized to standard treatment or to standard treatment plus ivabradine. HR was significantly reduced in ivabradine group, without modifying SAP.…”
Section: Discussionmentioning
confidence: 99%
“…A case report104 and a small randomized trial105 documented the heart rate-lowering effect of ivabradine in post-AMI CS patients and also reported some beneficial therapeutic effects.…”
Section: Clinical Efficacy Safety and Tolerability Of Ivabradine In Hfmentioning
confidence: 99%
“…In the prospective randomized trial,105, 58 patients with post-AMI CS in sinus rhythm and after primary percutaneous coronary intervention were treated either with standard medical treatment (28 patients) or with standard medical treatment plus ivabradine (30 patients; starting with 2.5 mg b.i.d.) given orally or – in mechanically ventilated patients – by nasogastric route.…”
Section: Clinical Efficacy Safety and Tolerability Of Ivabradine In Hfmentioning
confidence: 99%
“…Die alternative Gabe von Ivabradin erscheint hingegen als eine alternative Möglichkeit, die in kleineren Populationen und präliminären Arbeiten zum einen sicher durch eine Magensonde applizierbar war und ggf. sogar ein positives Outcome verspricht [46].…”
Section: Therapie Der Herzinsuffizienzunclassified